Instructors' perceptions on the implementation of continuous quality improvement plan to the support courses at Universiti Malaysia Perlis (UNIMAP) - Irma, Ahmad (2008)
Ever since UniMAP has decided to implement the Outcome Based Education (OBE) in a full swing, a lot of processes has to be implemented which begin with restructuring the curriculum and courses until preparing for assessment and evaluation tools, the collection of evidence and also continuous quality improvement (CQI). In UniMAP situation, CQI is referred to "closing the loops" and it is implemented at course level by collecting evidence from direct assessment tools. Although the CQI is specifically designed for the Engineering programmes, there is no exception for non-engineering courses for not doing it. Concerning that little is known regarding on the appropriateness and effectiveness of the CQI process towards the support courses and there is no single study has been conducted to examine the usability of the process whether it can fit in both engineering and non-engineering courses offered at UniMAP, thus this study was conducted to explore the appropriateness and effectiveness of the CQI process towards nonengineering courses. It used all the instructors who are responsible with the Diploma support courses as the focus group of the study. From the finding, most of the instructors have misconception on CQI which has lead to ineffective implementation of CQI process to the support courses at UniMAP. Ineffective leadership and inappropriate use of CQI tools have also effecting the implementation of CQI process. From the findings too, two of the instruments have been identified as inappropriate for the process. Finally, this study has suggested four recommendations in order to improve the implementation of CQI process for support courses. The recommendations are to conduct workshops and training courses, to develop a monitoring group and to allow for direct participation from the support courses' instructors in any discussions that related to CQI activities